Development and Implementation of Arsif Augmented Reality Learning Media to Support High School Students’ Critical Thinking, Creative Thinking, and Science Process Skills in Physics Learning - Rosynanda Nur Fauziah; Ficky Adi Kurniawan (Journal Of Education Research and Inovative, 2026)
This study aimed to develop and examine the feasibility and effectiveness of Arsif, an Android-based Augmented Reality application designed to support physics learning on the concept of special light rays. Arsif was developed to provide interactive visualization of physics concepts and to facilitate the improvement of students’ critical thinking, creative thinking, and science process skills. This study employed a quasi-experimental method with a pre-test and post-test nonequivalent control group design. The feasibility of the learning medium was assessed through expert validation involving media and material aspects. The results showed that Arsif obtained a validation score of 90% from the media expert and 92% from the material expert, indicating that the application was highly valid and feasible for use in physics learning. The implementation results showed an increase in students’ scores in all measured skills. Critical thinking skills increased from 32.3% in the pretest to 86.6% in the posttest, creative thinking skills increased from 20.8% to 69.9%, and science process skills increased from 59.1% to 80.1%. These findings indicate that Arsif has the potential to support students in understanding abstract physics concepts through interactive visualization while improving essential learning skills. Therefore, augmented reality-based learning media can be considered a promising alternative for creating more engaging, interactive, and meaningful physics learning experiences.